2018
DOI: 10.1021/acsami.8b11879
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Neighboring Substitution-Triggered Full Visible Spectrum Emission in Single-Phased Ca10.5–xMgx(PO4)7:Eu2+ Phosphors for High Color-Rendering White LEDs

Abstract: Manipulating the distribution of rare-earth activators in multiple cation lattices can achieve versatile color output for single-phased phosphor-converted white light-emitting diodes (LEDs). However, successful cases are barely reported, owing to the uncertain distribution of rare-earth activators and the special combination of three primary colors for white LEDs. Herein, we took whitlockite β-Ca(PO) as a multiple cation lattice host to manipulate the redistribution of Eu activators, and the surprising Mg-guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 53 publications
4
55
0
Order By: Relevance
“…The PLE, PL, together with DR spectra of LSA:0.02Eu 2+ are shown in Figure A. Two distinct characteristic excitation bands of Eu 2+ ions ranging from 250 to 350 nm are observed, which originate from the ground state 4 f 7 to the higher‐lying and lowest lying 4 f 6 5 d 1 states transition of Eu 2+ . It is also found that the PLE is in accordance with the DR spectrum.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The PLE, PL, together with DR spectra of LSA:0.02Eu 2+ are shown in Figure A. Two distinct characteristic excitation bands of Eu 2+ ions ranging from 250 to 350 nm are observed, which originate from the ground state 4 f 7 to the higher‐lying and lowest lying 4 f 6 5 d 1 states transition of Eu 2+ . It is also found that the PLE is in accordance with the DR spectrum.…”
Section: Resultsmentioning
confidence: 62%
“…Two distinct characteristic excitation bands of Eu 2+ ions ranging from 250 to 350 nm are observed, which originate from the ground state 4f 7 to the higher-lying and lowest lying 4f 6 5d 1 states transition of Eu 2+ . [32][33][34][35] It is also found that the PLE is in accordance with the DR spectrum. From the inset of Figure 4D, the sample can emit intense green light under the UV (320 nm) excitation, and the maximum emission peaks at 518 nm with a full width at half maximum (FWHM) of approximately 1351 cm −1 .…”
Section: Luminescencementioning
confidence: 94%
“…The development of new high-performance phosphor materials will promote the advance of white LEDs and thus further extend the impact of solid-state lighting technology in lighting, displays and other applications. Currently, the white LEDs fabricated by using blue LED chips and YAG:Ce 3+ yellow phosphors suffer from low color-rendering index (CRI < 80) and high correlated color temperature (CCT ≈ 6494 K) owing to the cyan gap and lack of the red-light component [4,5], whereas the alternative white LED devices based on the combination of ultraviolet (UV) LED chips with tricolor (red, green, and blue) phosphors encounter serious problems such as inevitable energy reabsorption and color variation [6][7][8][9]. Accordingly, it is urgent and challenging to discover new high-quality single-phased white-light-emitting materials with fullvisible-spectrum emission to construct high-CRI white LEDs.…”
Section: Xiaoyong Huangmentioning
confidence: 99%
“…Based on the above reasons, excellent performance and broadband emitting yellow phosphors [13][14][15][16][17][18] were prepared and investigated in detail by many researchers in recent years. For example, Wang's group reported a yellowemitting Li 2 CaSi 2 N 4 :Ce 3+ nitride phosphor with tunable extra-broad emitting and zero-thermal-quenching property [19].…”
Section: Introductionmentioning
confidence: 99%